2013
DOI: 10.1590/jvb.2013.044
|View full text |Cite
|
Sign up to set email alerts
|

Acesso vascular para hemodialise: o que ha de novo?

Abstract: The increasing life expectancy of patients with chronic diseases, including chronic renal failure, means that treatment methods are constantly being updated and improved. Long term hemodialysis has created the need to provide and maintain long lasting vascular access. Arteriovenous fistula is the first-choice option for hemodialysis and research has been conducted to attempt to increase the useful life of both fistula and catheter access methods. This article reviews the vascular access options and solutions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
(19 reference statements)
0
5
0
5
Order By: Relevance
“…About AVF infection monitoring, Sousa and collaborators (2015) [ 20 ] identified the need to observe for the presence of redness and swelling at puncture sites. Although AVF is associated with lower infection rates when related to prostheses or catheters [ 35 ], a high incidence of this event is still observed. A systematic review reported a median rate of total infections of 0.11 per 1000 patient-days [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…About AVF infection monitoring, Sousa and collaborators (2015) [ 20 ] identified the need to observe for the presence of redness and swelling at puncture sites. Although AVF is associated with lower infection rates when related to prostheses or catheters [ 35 ], a high incidence of this event is still observed. A systematic review reported a median rate of total infections of 0.11 per 1000 patient-days [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neste contexto, a indicação do cateter deve ser somente em casos de hemodiálise de urgência, ou enquanto uma fístula matura (11) .…”
Section: Discussionunclassified
“…Ressalta-se que a primeira punção da fístula é de competência exclusiva do enfermeiro (12) . Considera-se que a função do enfermeiro é promover o bem estar do paciente renal em tratamento hemodialítico, dentro dos seus limites e respeitando a opção de cada um, ressaltando que cada individuo é responsável pelo sucesso do seu tratamento (11) .…”
Section: Discussionunclassified
“…9 Adequate flow rates have a direct influence on the effectiveness of HD and, therefore, on morbidity and mortality of ESKD patients. 4 , 10 Several studies have analyzed the influence of preoperative examination and vein mapping on the patency of AVF. 11 - 14…”
Section: Introductionmentioning
confidence: 99%